CONTINUITIES AND CHANGES MUSICAL CULTURE OF MELAYU DELI - Agustono, Budi; Takari, Muh (Grenek: Jurnal Seni Musik, 2019)
This paper analyze about continuities and changes Malay North Sumatra musical culture, with historical and ethnomusicological approach. We use the evolution theory, and qualitative methods in this research. Malay music North Sumatran begun in the early of Malay culture, in 1300 B.C. By this time to the first century, Malay musical culture basic on animism and dynamism, which use to ceremony activities. In firs to thirteen century Hinduism and Buddhism come to Malay culture. In this era musical culture from Hinduism and Buddhism absorbed by Malay North Sumatran, in the form as follows: raga and tala influence, some instrumets from India as tabla, mrdanga, sarenggi, and so on. Then, 13th century Islam adopted by North Sumatran in musical culture. The concep One God and adat bersendikan syarak, syarak bersendikan kitabullah has been make the main role in custom and music. The concept maqam and iqaat adopted to Malay musical culture. Th 16th century European come to Malay World, and some musical genres adopted by Malay, as dondang sayang (from branyo Portuguese), ronggeng, popular music, and so on. Today, all of musical element fusion to Malay culture with new development aesthetics.